Selected Topics in Breastfeeding - Mauricio Barría, R. P. (IntechOpen, 2018)
Breastfeeding is a cornerstone of child nutrition and the growth and development of children. In addition, it generates other multiple benefits for both child and mother. Consequently, it has been recognized as a strategy of promotion and protection of the main health for different countries across the world. However, despite the strong evidence of its benefits and the public health policies being implemented to promote breastfeeding, the prevalence of exclusive breastfeeding at the sixth month does not reach the recommendations of many countries. This book intends to provide the reader with an overview of selected topics on current state-of-the-art breastfeeding in different situations and conditions. Specialists in the field of breastfeeding from different countries have developed these chapters and through them they share part of their experience.